α-Fetoprotein-Producing Endometrial Carcinoma Is Associated With Fetal Gut-Like and/or Hepatoid Morphology, Lymphovascular Infiltration, TP53 Abnormalities, and Poor Prognosis: Five Cases and Literature Review - Otani, Tomoyuki; Murakami, Kosuke; Shiraishi, Naoki; Hagiyama, Man; Satou, Takao; Matsuki, Mitsuru; Matsumura, Noriomi; Ito, Akihiko (Frontiers in Medicine, 2021)
The clinicopathological, immunohistochemical, and molecular characteristics of α-fetoprotein (AFP)-producing endometrial carcinoma (AFP+ EC) are poorly understood. From 284 cases of endometrial carcinoma in our pathology archive, we identified five cases (1.8%) of AFP+ EC with fetal gut–like (4/5) and/or hepatoid (2/5) morphology. All cases exhibited lymphovascular infiltration. In addition, 24 cases of endometrial carcinoma with elevated serum AFP levels were retrieved from the literature. The patient age ranged from 44 to 86 years (median: 63). Of 26 cases whose FIGO (International Federation of Gynecology and Obstetrics) stage and follow-up information was available (mean follow-up 24 months), 15 were stage I or II and 11 were stage III or IV. Even in stage I or II disease, death or relapse occurred in more than half of the patients (8/15). Detailed analysis of our five cases revealed that, on immunohistochemistry, AFP+ EC was positive for SALL4 (4/5), AFP (3/5), and HNF1β (4/5) in >50% of neoplastic cells and negative for estrogen and progesterone receptors (5/5), PAX8 (4/5), and napsin A (5/5). Four cases exhibited aberrant p53 immunohistochemistry and were confirmed to harbor TP53 mutations by direct sequencing. No mutation was found in POLE, CTNNB1, or KRAS. In conclusion, AFP+ EC merits recognition as a distinct subtype of endometrial carcinoma, which occurs in 1.8% of endometrial carcinoma cases, are associated with TP53 abnormalities, exhibit lymphovascular infiltration, and can show distant metastasis even when treated in early stage.